The effectiveness of social responsibility implementation in Wisma TM Mahkota, Kuantan / Wan Nur Izni Wan Ab. Majid - Wan Ab. Majid, Wan Nur Izni (2012)
Purpose – The purpose of this paper is to study on the effectiveness of social responsibility implementation in Wisma TM Mahkota, Kuantan.